2015
DOI: 10.1016/j.pmrj.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physiatry in Regenerative Medicine: The Past, The Present, and Future Challenges

Abstract: Historically, the foundation of physical medicine and rehabilitation training has provided the capabilities to optimize nonoperative treatments of a variety of musculoskeletal conditions, including acute and chronic muscle, tendon, ligament, and cartilage disorders. Such treatments include the use of nonsteroidal anti-inflammatory drugs (NSAIDs), therapeutic modalities (eg, thermal and manual therapies), and corticosteroid injections in conjunction with specific rehabilitation exercises. Although NSAIDs, modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…iv. Be up to date on the evidence-based medicine research and appropriate usage regarding orthobiologics [14][15][16][17][18]. c. Asthma medications.…”
Section: E Commonly Used Medicationsmentioning
confidence: 99%
“…iv. Be up to date on the evidence-based medicine research and appropriate usage regarding orthobiologics [14][15][16][17][18]. c. Asthma medications.…”
Section: E Commonly Used Medicationsmentioning
confidence: 99%
“…A recent review in PM&R stated that “Prolotherapy, PRP [platelet‐rich plasma], and mesenchymal stem cells are being used in the treatment of tendinopathies, ligament injuries, and degenerative joint disease, with an increasing number of both animal and clinical studies to support their use. Some evidence indicates that these treatments may be superior to the traditional treatment interventions from the ‘past’” [17]. That observation highlights the need for PM&R and other sports medicine specialists to be fully aware of the scientific evidence for such novel techniques and to continue to optimize the success of nonoperative treatment outcomes.…”
Section: The Current State Of Sports Medicinementioning
confidence: 99%
“…Various sources of stem cells have been used to treat a variety of medical conditions. Research is beginning to demonstrate that via an induced pluripotent stem cell technique, mesodermal cells such as chondrocytes can be generated by reprogramming a patient's own dermal fibroblasts, adipose tissue, or bone marrow [17]. Centeno and Faulkner [18] have suggested that recent advances in regenerative therapies include clinical trials for anterior cruciate ligament, rotator cuff, cartilage, and intervertebral disk defect repair and for the healing of meniscal tears.…”
Section: The Current State Of Sports Medicinementioning
confidence: 99%
“…The primary goal of physiatrists is to optimize the pain management of their patients with various MSK conditions, including acute and chronic muscle, tendon, ligament, and cartilage disorders. The traditional management of MSK pain involves control with conservative “Rest, Ice, Compression, Elevation” treatment and physical therapy to corticosteroid injections coupled with specific rehabilitation exercises [ 5 ].…”
Section: Introductionmentioning
confidence: 99%